Dynamic Analysis of Landing Autonomous Underwater Vehicle - 杜兵 蒋永翔 张宏伟 (Transactions of Tianjin University, 2012)
In autonomous underwater vehicles （AUVs） the onboard power used to complete missions is limited. To solve this problem, a landing AUV has been designed, which conserves energy by sitting on the seafloor while moni- toring the ocean. In order to study the dynamic behaviors for better control of the AUV, the dynamic analysis of the landing AUV is presented in this paper. Based on the momentum theorem and the angular momentum theorem, the dynamic model of the landing AUV is derived. The simulations of rectilinear motion, rotary motion and helix motion indicate the dynamic behaviors of the AUV. The ocean experiments validate the dynamic model presented in this pa- per. The experiments also verify that the landing AUV can work for a longer time than common AUVs.